Solve for one variable and plug it into the second equation...
So, let's solve the first equation for y:
-x + y = -4
y = x - 4
Now plug this into the second equation:
4x - 3(x - 4) = 13
Distribute through the parentheses:
4x - 3x + 12 = 13
Subtract 12 from both sides:
4x - 3x = 1
Simplify:
x = 1
Now plug this back into your original substitution:
y = x - 4
y = (1) - 4
y = -3
So your answer is x = 1 and y = -3.
You should double-check your answer....
-x + y = -4,
-(1) + (-3) =? -4
-4 = -4 <-- check
4x - 3y = 13
4(1) - 3(-3) =? 13
4 + 9 = 13 <-- check
So your answer is:
x = 1
y = -3
2006-11-06 11:49:52
·
answer #1
·
answered by Puzzling 7
·
0⤊
0⤋
Multiply the top equation by 3 to get
-3x +3y = -12 then add it to the bottom
x = 1 so y = -3
I'm not a fan of substitution for a problem like this
2006-11-06 11:51:21
·
answer #2
·
answered by MollyMAM 6
·
0⤊
0⤋
1) -x + y = - 4
2) 4x - 3y = 13
Solve equation 1 for y
y = x - 4
Substitute for y in equation 2
4x - 3(x - 4) = 13
4x - 3x + 12 = 13
x = 1
Put this result in equation 1
-x + y = - 4
-1 + y = - 4
y = -3
Check in equation 2
4(1) - 3(-3) = 13
4 + 9 = 13
13 = 13
2006-11-06 11:57:01
·
answer #3
·
answered by kindricko 7
·
0⤊
0⤋
-x + y = -4.......Eq 1
4x - 3y = 13.......Eq 2
Two simultaneous equations, two unknowns
Consider Eq 1.
-x + y = -4
-x = -4-y
x = 4 + y
Now substitute the value of 'x' in Eq.2
4x - 3y = 13
4(4 + y) - 3y = 13
16 + 4y - 3y = 13
16 + y = 13
y = 13 -16
y = -3
Now substitute the value of 'y' in Eq. 1 to find 'x'
-x + y = -4
-x -3 = -4
-x = -4+3
-x = -1
x= 1
(x = 1, y = -3)
2006-11-06 12:10:05
·
answer #4
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
0⤋
-x + y = -4 >>>>> y = x - 4
4x - 3y = 13
subst. first to second to find x
4x - 3y = 13
4x - 3(x - 4) = 13
4x - 3x + 12 = 13
x = 13 -12
x = 1
using first eqn.
y = x - 4
y = 1 - 4
y = -3
Therefore
x = 1
y = -3
2006-11-06 11:53:08
·
answer #5
·
answered by bhen 3
·
0⤊
0⤋
-x + y =-4 add x to both sides.
y= x-4
4x-3y =13 substitute in for y
4x-3(x-4) =13 multiply the brackets by -3.
4x-3x +12 =13 subtract 4 from both sides.
x =1
y=-3
2006-11-06 11:54:09
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
x = y + 4
4(y + 4) - 3y = 13
4y - 3y = 13 - 16
y = -3
Substitute in first equation
-x +(-3) = -4
x = 1
2006-11-06 11:54:51
·
answer #7
·
answered by Malcolm 1
·
0⤊
0⤋
First equation.
y = -4 + x
Not plug in (-4 + x) whereever u see "y" in the second equation and solve it.
Not going to do it. I'm too lazy
2006-11-06 11:50:06
·
answer #8
·
answered by Luken 5
·
0⤊
0⤋
-x + y = -4
y = x - 4
4x - 3(x - 4) = 13
4x - 3x + 12 = 13
x + 12 = 13
x = 1
y = 1 - 4
y = -3
ANS : (1,-3)
2006-11-06 11:50:52
·
answer #9
·
answered by Sherman81 6
·
0⤊
0⤋
y=-3
x=1
2006-11-06 11:53:54
·
answer #10
·
answered by AnSwERinho 3
·
0⤊
0⤋